Training to Create Teaching Media for Preschool Teachers Based on Visual Communication Technology - Darmawan, Ferry; Hakim, Arif; Sevtiany, Venny (KnE Social Sciences, 2023)
The advent of the Industrial Revolution 4.0 and its subsequent transition to the Society 5.0 era necessitates that PAUD (Early Childhood Education) teachers enhance their knowledge and skills in Communication Technology. To meet this demand, teachers are encouraged to create their own teaching media using visual communication technology instead of relying solely on pre-existing products, such as storybooks from bookstores produced by printing companies. A preliminary study in Cicalengka District, Bandung Regency, revealed that PAUD teachers face challenges in developing information technology-based learning media. Therefore, this study aims to improve the skills of PAUD teachers in creating independent teaching media using Visual Communication Technology. The research includes ten teachers from Raudhatul Athfal in Cicalengka District as the study subjects. The research method employed is descriptive-analytic, and data collection techniques involve the use of test equipment. The analysis is conducted using different tests to assess the impact of the training. The study’s results demonstrate a significant improvement in PAUD teachers’ knowledge after undergoing training in creating teaching media based on visual communication technology. As a result, this training activity is highly beneficial for PAUD teachers in Cicalengka District. Keywords: information and communication technology, early childhood teacher, independent teaching media, visual communication